Long-term changes in the dentoalveolar system of rats after experimental intra-abdominal hypertension - N. S. Morozova; A. A. Mamedov; D. Y. Lakomova; L. D. Maltseva; O. L. Morozova (Сеченовский вестник, 2021)
Aim. To establish the effect of experimental intra-abdominal hypertension (IAH) on the teeth-jaw system of rats in the long-term period based on the study of pro-inflammatory cytokines and morphological analysis of the elements of the temporomandibular joint (TMJ) and salivary glands.Materials and methods. The experiment was carried out on 60 newborn rats; IAH was modelled by injecting collagen into the abdominal cavity to a predetermined level of intra-abdominal pressure. The rats were evenly (n = 20) divided into 3 groups: 1st - control; 2nd and 3rd - with light and severe IAH, respectively. Serum levels of IL-18, MCP-1, NGAL were determined by multiplex analysis after 10 and 120 days, VEGF-C - after 10 days - by ELISA. The morphological examination of the TMJ and salivary glands was performed using a Leica DM2000 microscope after 120 days.Results. After 10 days and 120 days, blood serum levels of NGAL, IL-18 and MCP-1 were statistically significantly increased in groups 2 and 3 compared to the control; the concentration of MCP-1 increased in proportion to the severity of the IAH with the maximum values in group 3. After 10 days, the level of VEGF was significantly increased in group 2 compared to the control group (p < 0.02). Inflammation of the TMJ was observed significantly more often in groups 2 and 3 than in the control group (p = 0.0002). In group 3, circulatory disorders and bone marrow degeneration of the TMJ, as well as inflammation, circulatory disorders and hyperplasia of the lymphoid tissue of the salivary glands were statistically significantly more often compared to groups 1 and 2.Conclusion. In the long term, experimental IAH showed an increase in the levels of markers of inflammation and hypoxia in the blood serum of rats; the severity of synovitis and sialadenitis grew with an increase in the level of intra-abdominal pressure; the maximum deviations in inflammation markers and morphological changes in the TMJ and salivary glands of rats were observed in the group with severe IAH.